Deep differentiation between and within Mediterranean glacial refugia in a flying mammal, the Myotis nattereri bat complex. (27th December 2012) - Salicini, Irene; Ibáñez, Carlos; Juste, Javier; Masters, Judith
Abstract Aim The role of glacial refugia in the biogeographical patterns in the Western Palaearctic region has been widely discussed, but many questions remain unresolved. We examined the biogeography, genetic diversity, spatial distribution and evolutionary history of the Myotis nattereri bat species complex to investigate the presence of multiple refugia and the persistence of Quaternary differentiation between and within Mediterranean refugia in a flying mammal. Location Western Palaearctic region (central and southern Europe and north‐western Maghreb). Methods We analysed three mitochondrial fragments (cytochrome b, NADH dehydrogenase subunit 1 and the control region; 1570 bp) from 136 individuals of the M. nattereri complex sampled from 87 different localities using a range of phylogenetic techniques. Divergences among clades were also dated using a Bayesian coalescence approach. Results Phylogenetic analyses identified four main lineages, coincident with the four cryptic species recently described. Each species is further subdivided into well‐supported lineages with evident geographical structure. Estimates of genetic diversity and polymorphism were very high for the majority of subclades, with the exception of M. nattereri s.s. Main conclusions The M. nattereri bat complex comprises four species whose distributions in the Western Palaearctic correspond to four main glacial refugia (Iberia, Italy, Balkans and Morocco). These species are the result of long‐term isolation (remarkable in a flying mammal) over several glacial cycles. The Balkan species expanded into central Europe in a rapid recolonization process. Both the Iberian and Italian peninsulas show a clear pattern of refugia‐within‐refugia in their genetic structuring, with a deeply differentiated southern Italian clade. Morocco shows two markedly differentiated lineages, probably separated by the Atlas Mountains. The legacy of Pleistocene cycles is evident in both the speciation and the intraspecific diversification events.